2020
DOI: 10.1021/acsmacrolett.0c00543
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Formation and Growth Kinetics of Polyelectrolyte Complex Micelles with Millisecond Resolution

Abstract: We have directly observed the in situ self-assembly kinetics of polyelectrolyte complex (PEC) micelles by synchrotron time-resolved small-angle X-ray scattering, equipped with a stopped-flow device that provides millisecond temporal resolution. A synthesized neutral-charged diblock polycation and homopolyanion that we have previously investigated as a model chargematched, core−shell micelle system were selected for this work. The initial micellization of the oppositely charged polyelectrolytes was completed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 46 publications
4
27
0
Order By: Relevance
“…Tirrell and co-workers conducted time-resolved SAXS experiments on longer dbps (PVBTA 53 - b -PEO 112 and PVBTA 100 - b -PEO 225 ) mixed with the weak polyelectrolyte PAA 158 . 67 In good agreement with their molecular dynamics simulations, the trSAXS experiments showed charge-neutral clusters formed within the 100 ms of experimental dead time, which rearranged into small equilibrium micelles ( R H = 10 nm) within a matter of seconds. The kinetic profiles also suggested that micellar fusion–fission events are unlikely.…”
Section: Association and Dissociation Pathwayssupporting
confidence: 73%
See 1 more Smart Citation
“…Tirrell and co-workers conducted time-resolved SAXS experiments on longer dbps (PVBTA 53 - b -PEO 112 and PVBTA 100 - b -PEO 225 ) mixed with the weak polyelectrolyte PAA 158 . 67 In good agreement with their molecular dynamics simulations, the trSAXS experiments showed charge-neutral clusters formed within the 100 ms of experimental dead time, which rearranged into small equilibrium micelles ( R H = 10 nm) within a matter of seconds. The kinetic profiles also suggested that micellar fusion–fission events are unlikely.…”
Section: Association and Dissociation Pathwayssupporting
confidence: 73%
“…Interestingly, this second, slow relaxation process was concentration-independent, suggesting that the equilibration is driven mainly by the exchange of polymer chains rather than fusion and fission of (pre)­micelles. Tirrell and co-workers conducted time-resolved SAXS experiments on longer dbps (PVBTA 53 - b -PEO 112 and PVBTA 100 - b -PEO 225 ) mixed with the weak polyelectrolyte PAA 158 . In good agreement with their molecular dynamics simulations, the trSAXS experiments showed charge-neutral clusters formed within the 100 ms of experimental dead time, which rearranged into small equilibrium micelles ( R H = 10 nm) within a matter of seconds.…”
Section: Association and Dissociation Pathwaysmentioning
confidence: 69%
“…Taken together, these results indicate that the parent droplets recruited anionic free chains, cationic growing chains, and the nascent clusters via a kinetically dictated “repulsion–insertion mechanism" as described by Tirrell and Lund, leading to the kinetically dictated condensation-driven hierarchical assembly through the programmed recruitment of these active gradients from the dynamic evolving aqueous medium of LLPS-PIESA.…”
supporting
confidence: 56%
“…PEC hydrogels self-assemble swiftly [65][66][67][68] upon mixing of aqueous solutions of oppositely charged block polyelectrolytes (bPEs) based on poly(ally glycidyl ether)98poly(ethylene oxide)455-poly(ally glycidyl ether)98 (PAGE-PEO-PAGE). The PAGE blocks were functionalized with ionic (guanidinium and sulfonate) moieties [1] (Figure 1A, row 1).…”
Section: Crosslinkable Polymersmentioning
confidence: 99%